Measuring non monetary innovation in software: A case study in floss firms from Argentina - Motta, Jorge Jose (2019)
This paper presents a critical review of the design of innovation surveys that follow the Oslo Manual standards, based on a series of case studies in Free/Libre Open Source Software (FLOSS) companies. The main objective of the article is to propose criteria for measuring innovation in software that consider the specificities of the non-monetized innovation generated in the FLOSS community, helping to overcome relevant limitations of the current sectorial surveys based on the Oslo Manual. We applied a qualitative analysis based on seven case studies in FLOSS firms from Argentina, mainly through semi-structured interviews to key informants. Such analysis was aimed to elucidate the nature and particularities of the innovation processes and outcomes in the firms, the characteristics of the collaboration with the community and its role in the business model and innovation strategy of the organizations. The main results of the empirical study are: a) a criticism of the monetary conception of the predominant innovation in the manuals of the area and b) on this basis emerges a series of recommendations to improve the measurement of innovation through surveys in the software sector , such as: the consideration of publicly released products and developments and contributions to third-party products in the FLOSS community, the incorporation of performance indicators of firms not based on sales from innovation, and the consideration of innovation selection mechanisms typical of FLOSS communities not based on their market impact.